Fabrication and Uniaxial Tensile Properties of Soldered Porous Copper Fiber-Sintered Sheets - Ruiliang Liu; Wei Zhou; Shuangli Li; Dongsheng Xu (Advances in Materials Science and Engineering)
Porous copper fiber-sintered sheets (PCFSSs) with different porosities were fabricated through the solid-phase sintering method using cutting copper fibers. PCFSSs with the same porosity and different porosities were then joined via a fluxless soldering method. By analyzing the uniaxial tensile property of the PCFSSs, the formation mechanism of the soldered PCFSSs was investigated. The difference in the tensile properties between the soldered and original PCFSSs was examined. Experimental results indicated that, for the PCFSSs with homogeneous porosity, reducing the porosity increased the tensile strength and elongation at break significantly. The fluxless soldering method with the lead-free solder resulted in excellent joining of the PCFSSs with the same porosity and different porosities. Moreover, the final tensile strength of the soldered PCFSSs with the same porosity was nearly equal to that of their parent PCFSSs. The tensile strength of the soldered PCFSSs with different porosities depended on the higher-porosity section. After soldering the PCFSSs, Young’s modulus increased and the elongation at break reduced.